Spatial Ability Differences in Athletes and Non-Athletes - Jessica Cynthia; Leonardo Lubis; Vitriana Vitriana (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Cognitive processes, specifically spatial abilities, are responsible for integration of daily activities. Many factors contribute to the plasticity of the brain which, furthermore, alter the spatial ability. Physical activity, which can be further grouped into sport and exercise, is a modifiable factor that enhances the cognitive processes through a divergent mechanism. This study aimed to gain further understanding on whether sport differs from exercise in altering spatial ability in athletes and non-athletes.Methods: This observational study compared the spatial ability score of athletes of Indonesia National Sport Comitte (Komite Olahraga Nasional Indonesia, KONI) in West Java (n= 21) and non-athletes (n= 21). Sampling were performed using stratified random technique and data were collected between August and October 2015 which included spatial scores and demographic of subjects.Results: The difference in spatial scores between athletes and non-athletes were not significant (p=0.432).Conclusions: This study suggests an insignificant difference in spatial ability in athletes performing sport and non-athletes performing exercise. Hence, the cognitive component skills in sport experience do not alter the spatial ability. [AMJ.2016;3(4):533–7] DOI: 10.15850/amj.v3n4.934